Resilience in Wives with Homosexual Husband - Muhamad Fikri Maulana; A. Rachmad Djati Winarno; Sri Sumijati (Muwazah, 2022)
A family full of peace, purity, love & affection, belonging, and so on is the goal of marriage that is coveted by all couples. But not all families and happy marriages work. There are many reasons, one of which is knowing that her husband is a homosexual. In general, wives who know their husband's identity often experience emotional turmoil such as disappointment, stress, depression to the meaninglessness of life, although in particular there are those who can rise from this suffering. This study aims to determine the condition of the wife's resilience with a homosexual husband and the factors that influence it. This study uses a qualitative method with a phenomenological approach. Participants in this study found two wives who had homosexual husbands. Data collection is based on interviews and observations conducted directly at the place where the participants are domiciled, namely Jepara and Batang and through video calls. The results of this study indicate that both participants are able to develop resilience based on aspects such as emotional regulation, impulses, optimism, causal analysis, empathy, self-efficacy and control and are influenced by I Am, I Have, and I Can factors. The collaboration factor of personality, love, spirituality, family support, social support, communication skills and independence became the key for both participants to be able to develop resilience and go through the dark period of suffering to a brighter life.